(untitled) (PERcursos Linguísticos, 2025)
This work is part of the activities of the Language, Culture, History and Power – LINCHI study group, responsible for the project Toponymic Atlas of the State of Maranhão: Analysis of Macro and Microtoponymy, developed at the State University of Maranhão, Brazil. The study presents names of small human settlements and physical features present in the city of Riachão, Maranhão, Brazil, a municipality in which there are large numbers of waterfalls and rich aquifers, located in the center of the tourist center called “Caminho das Águas”, in the Chapada das Mesas region. This potential instigates the investigation of the names of these places, with the classification and analysis of the characteristic hydronyms, oronyms and microtoponyms, based on the onomastic-toponymic theory with the methodological postulates of Dick (1990, 1992) and Isquerdo (2012), in which a taxonomic classification is carried out in a qualitative and quantitative approach. The objective is to present the contributions raised for the preparation of the aforementioned atlas, specifically selecting the names, identifying the motivations for the names and classifying them according to the taxonomies, subdividing them into two classification groups: taxonomies of a physical nature (names related to the natural environment) and of an anthropocultural nature (related to human activities). Through documentary research in the official database of the Brazilian Institute of Geography and Statistics (IBGE).